Eripisela porcina: protección vacunal de tres preparados comerciales frente a serotipos aislados en Chile - Abalos P., Pedro; Sánchez Ch., María Luisa; Mora S., Patricia; Pinochet V., Lautaro (Monografías de Medicina Veterinaria, 1993)
Three erysipelas comercial vaccines used in Chile were tested in mice against a challenge with strains of serotypes 2, 19, 10 and 14 of Erysipelotrix rhusiopathiae isolated in the country. Strains of serotypes 2 and 19 were isolated from the tonsils of healthy pigs and those of serotypes 10 and 14 were found in arthritic joints of pigs. It was shown that not all the vaccines protected efficiently against the challenge, in spite of using two different doses of the product. Protection was complete with all the vaccines considered using serotype 2 as challenge and only one of them protected completely against serotype 19. When the challenge was done with serotypes 10 and 14, there was less protection in two of the vaccines tested. The use of an appropriate product is recommended to protect not only against the acute disease but also against chronic affections produced by E. rhusiopathiae Key words: Erysipelothrix rhusiopathiae, serotypes, vaccines.